Structural characteristic and phylogenetic analysis of the complete chloroplast genome of Dianthus Caryophyllus. Issue 2 (3rd July 2018) - Chen, Shuwen; Xu, Zhenggang; Zhao, Yunlin; Zhong, Xiaofen; Li, Chaoyang; Yang, Guiyan
Abstract: Chloroplast genomes are widely used in genetic engineering, molecular marker development, and phylogeny. In order to analyze the complete chloroplast genome of Dianthus caryophyllus, the complete chloroplast genome of D. caryophyllus was sequenced and annotated. On the other hand, phylogenetic analysis of the chloroplast genome of D. caryophyllus was carried out. The results showed that the whole length of the chloroplast genome of D. caryophyllus was 147, 604 bp, and had a typical conserved quadripartite structure. The G and C basic content of D. caryophyllus chloroplast was 36.3%. The genome contained 83 protein-coding genes, 34 tRNA genes, and 6 rRNA genes. Among the protein-coding genes, 10 genes contain a single intron and 2 genes contain two introns. The phylogeny of D. caryophyllu s indicated that the closest phylogenetic relationship was D. longicalyxanus . This study provides materials for the molecular study of D. caryophyllus may improve the carnation industry.